Régimes de qualité de l’emploi et diversité des pays émergents - Thibaud Deguilhem; Adrien Frontenaud (Revue de la Régulation)
Emerging countries and their leaders, the BRICS, can be revisited with an institutionalist approach enabling a better recognition of their diversity. Focusing on the composition of their labour nexus, this paper offers to question the category formed by these countries by studying their variety of quality of employment regimes. Two interesting results came out from this study using a Principal Components Analysis (PCA) and a Mixed Clustering (MC) break two institutional dimensions into fourteen indicators. (1) Four specific quality of employment regimes appear, illustrating their heterogeneity and the weakness of this category. (2) The BRICS appear notably scattered over some socio-economic aspects of each leader. Far from composing a coherent and independent regime, BRICS countries dispersion can be explained by a specific combination of socio-economic and institutional factors to each one of them.